2006
DOI: 10.1111/j.1600-6143.2006.01512.x
|View full text |Cite
|
Sign up to set email alerts
|

Culture Medium Modulates Proinflammatory Conditions of Human Pancreatic Islets Before Transplantation

Abstract: A portion of transplanted islets is lost during engraftment as a result of stressful events, involving hypoxia and production of proinflammatory molecules by islets. Two of these molecules (monocyte chemoattractant protein-1, CCL2/MCP-1 and tissue factor, TF) are directly correlated with reduced graft function. We evaluated which factors reduce islet proinflammatory conditions. In particular the effects of different culture media supplemented with proteins or antioxidant agents on CCL2/MCP-1 and TF human islet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…Treatment of islets with antioxidants [164,166,167] or anti-inflammatory agents [168,169] promotes islet survival by reducing the infiltration of macrophages and production of proinflammatory cytokines [170]. The protease inhibitor a1-antitrypsin inhibits thrombin, and promotes early graft survival [171].…”
Section: Loss Of Beta Cells During Islet Isolation and Primary Non-fumentioning
confidence: 99%
“…Treatment of islets with antioxidants [164,166,167] or anti-inflammatory agents [168,169] promotes islet survival by reducing the infiltration of macrophages and production of proinflammatory cytokines [170]. The protease inhibitor a1-antitrypsin inhibits thrombin, and promotes early graft survival [171].…”
Section: Loss Of Beta Cells During Islet Isolation and Primary Non-fumentioning
confidence: 99%
“…In the study by Winter et al [42] , the combined administration of vitamin C and E, but not vitamin A and selenium, led to a significant improvement in functional islet graft survival, associated with augmented islet engraftment. In contrast, Brown et al [40] and Marzorati et al [26] showed that the combination of vitamin E and C was unable to improve graft survival or decrease in-vitro MCP-1 release, respectively.…”
mentioning
confidence: 94%
“…metabolites and enzyme systems as well as reacting directly with oxidants in the cells. When GSH was added to culture medium, in contrast to vitamin E and C, it reduced MCP-1 [26] . L-glutamine as a precursor of GSH was shown to increase islet yield when added intra-ductally during human pancreatic islet isolation.…”
Section: Rat → Ratmentioning
confidence: 99%
See 2 more Smart Citations